Importancia de la domótica en el sistema eléctrico residencial, para desarrollar competencias básicas en los estudiantes de primer año bachillerato de la Unidad Educativa Eugenio Espejo de la ciudad de Babahoyo - Filian Macías, Gorbi Gualberto (2017)
Home automation in the residential electrical system is an automation system applied to the elements involved in an electrical installation, within the educational context allows to the students to develop basic skills competitions, and to function as a person skilled in solving problems, be these practical, intellectuals or of any kind, in addition the study and knowledge of this system will allow him to excel in the work sphere. The relevant information provided by home automation, easily accessible and comprehensible, will allow anyone who ventures into this technology to combine this knowledge with those already learned in the electrical part. The contents learned along with the skills and abilities acquired through their practices will be reflected in the development of demonstrated capabilities during their study period. In the Eugenio Espejo Educational Unit of the Babahoyo City, due process has not been carried out to allow the teachers to obtain knowledge that awakens the concern and encourages them to discover new technological knowledge for their good competitive development, thus generating students affected and pay little interest in the tasks entrusted by the teachers.